Permanent leadless cardiac pacing: results of the LEADLESS trial - Reddy, Vivek Y; Knops, Reinoud E; Sperzel, Johannes; Miller, Marc A; Petru, Jan; Simon, Jaroslav; Sediva, Lucie; de Groot, Joris R; Tjong, Fleur V Y; Jacobson, Peter; Ostrosff, Alan; Dukkipati, Srinivas R; et al. (Circulation, 2014)
BACKGROUND: Conventional cardiac pacemakers are associated with several potential short- and long-term complications related to either the transvenous lead or subcutaneous pulse generator. We tested the safety and clinical performance of a novel, completely self-contained leadless cardiac pacemaker. METHODS AND RESULTS: The primary safety end point was freedom from complications at 90 days. Secondary performance end points included implant success rate, implant time, and measures of device performance (pacing/sensing thresholds and rate-responsive performance). The mean age of the patient cohort (n=33) was 77±8 years, and 67% of the patients were male (n=22/33). The most common indication for cardiac pacing was permanent atrial fibrillation with atrioventricular block (n=22, 67%). The implant success rate was 97% (n=32). Five patients (15%) required the use of >1 leadless cardiac pacemaker during the procedure. One patient developed right ventricular perforation and cardiac tamponade during the implant procedure, and eventually died as the result of a stroke. The overall complication-free rate was 94% (31/33). After 3 months of follow-up, the measures of pacing performance (sensing, impedance, and pacing threshold) either improved or were stable within the accepted range. CONCLUSIONS: In a prospective nonrandomized study, a completely self-contained, single-chamber leadless cardiac pacemaker has shown to be safe and feasible. The absence of a transvenous lead and subcutaneous pulse generator could represent a paradigm shift in cardiac pacing. CLINICAL TRIAL REGISTRATION URL: http://clinicaltrials.gov. Unique identifier: NCT01700244.
Keywords: senioři; senioři nad 80 let; design vybavení; srdeční arytmie; Pacemaker, Artificial; Incidence; Cohort Studies; výsledek terapie; Middle Aged; mužské pohlaví; pacemaker; incidence; Prospective Studies; Arrhythmias, Cardiac; studie proveditelnosti; Equipment Design; kohortové studie; Postoperative Complications; Follow-Up Studies; cardiac; následné studie; Aged, 80 and over; ženské pohlaví; Humans; prospektivní studie; kardiostimulátor; Feasibility Studies; lidé středního věku; Female; Aged; Treatment Outcome; pooperační komplikace; lidé; Male